Parenting for Lifelong Health for young children: a randomized controlled trial of a parenting program in South Africa to prevent harsh parenting and child conduct problems - Cluver, Lucie (2020)
Background: Parenting programs suitable for delivery at scale in low‐resource contexts are urgently needed. We conducted a randomized trial of Parenting for Lifelong Health (PLH) for Young Children, a low‐cost 12‐session program designed to increase positive parenting and reduce harsh parenting and conduct problems in children aged 2–9. Methods: Two hundred and ninety‐six caregivers, whose children showed clinical levels of conduct problems (Eyberg Child Behavior Inventory Problem Score, >15), were randomly assigned using a 1:1 ratio to intervention or control groups. At t0, and at 4–5 months (t1) and 17 months (t2) after randomization, research assistants blind to group assignment assessed (through caregiver self‐report and structured observation) 11 primary outcomes: positive parenting, harsh parenting, and child behavior; four secondary outcomes: parenting stress, caregiver depression, poor monitoring/supervision, and social support. Trial registration: ClinicalTrials.gov (NCT02165371); Pan African Clinical Trial Registry (PACTR201402000755243); Violence Prevention Trials Register (http://www.preventviolence.info/Trials?ID=24). Results: Caregivers attended on average 8.4 sessions. After adjustment for 30 comparisons, strongest results were as follows: at t1, frequency of self‐reported positive parenting strategies (10% higher in the intervention group, p = .003), observed positive parenting (39% higher in the intervention group, p = .003), and observed positive child behavior (11% higher in the intervention group, p = .003); at t2, both observed positive parenting and observed positive child behavior were higher in the intervention group (24%, p = .003; and 17%, p = .003, respectively). Results with p‐values < .05 prior to adjustment were as follows: At t1, the intervention group self‐reported 11% fewer child problem behaviors, 20% fewer problems with implementing positive parenting strategies, and less physical and psychological discipline (28% and 14% less, respectively). There were indications that caregivers reported 20% less depression but 7% more parenting stress at t1. Group differences were nonsignificant for observed negative child behavior, and caregiver‐reported child behavior, poor monitoring or supervision, and caregiver social support. Conclusions: PLH for Young Children shows promise for increasing positive parenting and reducing harsh parenting